What management is : how it works and why it's everyone's business - Magretta, Joan, 1948-; Stone, Nan Dundes (London : Profile Books, 2003)
In 'What Management Is', Magretta distils the wisdom of a bewildering sea of books and articles into one simple, clear volume, explaining both the logic of successful organizations, and how that logic works in practice.
Originally published in Great Britain by HarperCollins Business 2002.
Includes bibliographical references and index.
Keywords: Management; Industrial management; Organisation and administration; Gestion; Gestion d'entreprise.; management; Industrial management; Management